Recent Updates in Experimental Research and Clinical Evaluation on Drugs for COVID-19 Treatment - Zou, Houwen; Yang, Yuqi; Dai, Huiqiang; Xiong, Yunchuang; Wang, Jing-Quan; Lin, Lusheng; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2021)
Since the outbreak of corona virus disease 2019 (COVID-19) in Wuhan (China) in December 2019, the epidemic has rapidly spread to many countries around the world, posing a huge threat to global public health. In response to the pandemic, a number of clinical studies have been initiated to evaluate the effect of various treatments against COVID-19, combining medical strategies and clinical trial data from around the globe. Herein, we summarize the clinical evaluation about the drugs mentioned in this review for COVID-19 treatment. This review discusses the recent data regarding the efficacy of various treatments in COVID-19 patients, to control and prevent the outbreak.